Mixed-method precooling enhances self-paced 20-km cycling time-trial performance when apparent temperature is >46°C but may not be a priority in <46°C - Ramos, J. A. P.; Ducker, K. J.; Riddell, H.; Girard, O.; Landers, G. J.; Brade, C. J. (International Journal of Sports Physiology and Performance, 2024)
Purpose Precooling (PreC) may only benefit performance when thermal strain experienced by an individual is sufficiently high. We explored the effect of mixed-method PreC on 20-km cycling time-trial (CTT) performance under 3 different apparent temperatures (AT).